Re‐evaluation of the prognostic significance of retropharyngeal node metastasis in nasopharyngeal carcinoma patients treated with intensity‐modulated radiotherapy. Issue 2 (19th September 2021) - Chen, Bijuan; Zhan, Zhouwei; Pan, Jianji; Xiao, Youping; Tang, Linbo; Guo, Qiaojuan; Xu, Yun; Zong, Jingfeng; Zhang, Ruiting; Xu, Hanchuan; Lin, Shaojun
Abstract: Background and Purpose: To investigate the prognostic value of retropharyngeal lymphadenopathy in nasopharyngeal carcinoma (NPC) after intensity‐modulated radiotherapy. Materials and Methods: Retrospective studies were performed in a total of 1197 patients. We evaluated the incidence of the retropharyngeal node (RPN) metastasis and the characteristics of the metastatic RPN including laterality, size, necrosis, and extranodal neoplastic spread. Results: RPN metastasis occured in 86.3% of patients. The RPN and level II metastasis shared similar survival outcomes. RPN metastasis was an independent prognostic factor for distant failure (hazard ratio = 1.615; 95% confidence interval, 1.063–2.452; P  = 0.025), in which the laterality of RPN metastasis significantly influences both the distant failure ( P  = 0.006) and disease progression ( P  = 0.001). In N1 disease, the occurrence of unilateral and bilateral RPN metastasis resulted in significantly different outcomes of the disease‐specific survival ( P  = 0.045) and progression‐free survival ( P  = 0.049). The co‐occurrence of bilateral RPN and cervical lymph nodes (CLN) metastasis was an independent adverse prognostic factor ( P  < 0.01) for distant failure and disease progression but not for locoregional recurrence. Conclusion: Both the RPN and level II are the first stations of NPC lymph node metastasis. For N1‐stage NPC patients, RPN metastasis, especially co‐occurrence of bilateral RPN and CLN metastasis, have an adverse influence on survival outcomes. Abstract : We first reported co‐occurrence of bilateral RPN and CLN metastasis had a bad influence for nasopharyngeal carcinoma in N1 disease.